Spatial variations in organic matter sources and biogeochemical processes in the East Sea - Choi, Jiyoung; Yi, Bo-Yeon; Kim, Yuri; Jeong, Eun-Je; Um, In-Kwon (Frontiers in Marine Science, 2025)
In this study, the spatial variations in total organic carbon (TOC), stable carbon isotopes (δ¹³Corg), C/N ratios, and nitrogen isotopes (δ¹⁵Norg) in East Sea sediments are examined to elucidate the sources, preservation, and diagenetic processes of organic matter. To this end, surface sediment samples were collected from the coastal regions of the East Sea using a box corer and analyzed for TOC, TON, stable isotopes (δ¹³C, δ¹⁵N), and grain size. The study region is categorized into three zones based on sediment characteristics: Zone A (straits), Zone B (northern coastal regions), and Zone C (central Ulleung Basin). Zone A, characterized by coarse sediments and dynamic hydrodynamic conditions, exhibits the lowest TOC (0.67%) and enriched δ¹³Corg values (-20.67‰). Zone B, influenced by coastal inputs, has moderate TOC (2.09%), slightly depleted δ¹³Corg (-21.09‰), and higher C/N ratios (6.30). Zone C, dominated by fine-grained mud sediments, features slightly lower TOC (1.96%), along with the most depleted δ¹³Corg (-21.86‰). Stable isotope analyses reveal that autochthonous particulate organic matter (POM) from marine phytoplankton is the primary source of organic matter in the East Sea. δ¹³Corg values (-23.15‰ to -20.33‰) align with phytoplankton-derived POM (-25‰ to -22‰), highlighting significant marine primary production contributions. In contrast, allochthonous inputs from atmospheric deposition, the Tsushima Warm Current, and rivers contribute approximately 82 gC/m²/year compared to 273 gC/m²/year from autochthonous sources. Seasonal δ¹³C variations are strongly correlated with peaks in primary productivity during spring and autumn. The study reveals differences between coastal (Zone B) and offshore (Zone C) regions in productivity regimes, nutrient utilization, and depositional settings. Coastal regions with high productivity show enriched δ¹³Corg, while offshore areas preserve isotopically lighter organic matter owing to stable depositional environments. Understanding the biogeochemical processes in the East Sea is essential for elucidating carbon cycling and its ecosystem implications. As a marginal sea with unique sedimentary dynamics, the East Sea serves as a natural laboratory for studying organic matter preservation. The findings provide insights into past and present carbon cycling and support predictions of future environmental changes under shifting climatic conditions.